Person–Job Fit and Work Stress on Employee Job Satisfaction Through Work Motivation: A Study of Employees at UPT Puskesmas Dapurang - Nur Aqsa; Rosanty, Niluh Putu Evvy; Natsir, Syahir; Murad, Moh. Ali (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of person–job fit and work stress on job satisfaction, with work motivation as a mediator, among employees at UPT Puskesmas Dapurang. Using a quantitative survey, data were collected through five-point Likert-scale questionnaires and analyzed using PLS-SEM. The findings show that person–job fit positively affects work motivation and job satisfaction, while work stress negatively affects both. Work motivation positively influences job satisfaction and mediates the effects of person–job fit and work stress. Therefore, improving job fit and managing work stress are important for enhancing employee motivation and job satisfaction. Keywords: Person-Job Fit; Work Stress; Work Motivation; Job Satisfaction; Partial Least Squares (PLS)